DIVIDEND POLICY AND CORPORATE GOVERNANCE: INTERNATIONAL EXPERIENCE AND APPLICATION TO UZBEKISTAN - Abdugafforov Otabek Dilshodbek ugli (Research Focus International Scientific Journal, 2024)
This study examines the relationship between dividend policy and corporate governance, with a focus on the international experience and its application to Uzbekistan. By analyzing a comprehensive dataset from diverse global markets, the research identifies best practices and key determinants of effective dividend policies within the framework of robust corporate governance. The methodology includes a comparative analysis of governance structures and dividend distribution strategies across developed and emerging economies. In the context of Uzbekistan, the study evaluates the current state of corporate governance and its influence on dividend policy decisions. The findings reveal significant variations in dividend practices influenced by governance mechanisms, regulatory environments, and market maturity. Recommendations are provided for Uzbekistan to enhance its corporate governance standards and optimize dividend policies to attract foreign investment and promote sustainable growth.